Structure of the transcription activator target Tra1 within the chromatin modifying complex SAGA. Issue 1 (December 2017) - Sharov, Grigory; Voltz, Karine; Durand, Alexandre; Kolesnikova, Olga; Papai, Gabor; Myasnikov, Alexander; Dejaegere, Annick; Ben Shem, Adam; Schultz, Patrick
Abstract The transcription co-activator complex SAGA is recruited to gene promoters by sequence-specific transcriptional activators and by chromatin modifications to promote pre-initiation complex formation. The yeast Tra1 subunit is the major target of acidic activators such as Gal4, VP16, or Gcn4 but little is known about its structural organization. The 430 kDa Tra1 subunit and its human homolog the transformation/transcription domain-associated protein TRRAP are members of the phosphatidyl 3-kinase-related kinase (PIKK) family. Here, we present the cryo-EM structure of the entire SAGA complex where the major target of activator binding, the 430 kDa Tra1 protein, is resolved with an average resolution of 5.7 Å. The high content of alpha-helices in Tra1 enabled tracing of the majority of its main chain. Our results highlight the integration of Tra1 within the major epigenetic regulator SAGA. The transcription co-activator complex SAGA is recruited to promoters by transcriptional activators and promotes the formation of the pre-initiation complex. Here, the authors present the cryo-EM structure of the SAGA complex and resolve the major target of activator binding, the 430 kDa Tra1 protein.